PENGARUH MATERIAL COST DAN PRODUCTION LABOR COST PADA PENENTUAN HARGA JUAL PRODUK FRAME - Tantri Ciptaning Pangesti; Suwardi - Suwardi; Yusmar Ardhi Hidayat (Admisi dan Bisnis, 2018)
Selling price determination must be able to cover total costs, fluctuations of material cost and consider profit for company. PT Harrison & Gil Java Semarang needs to identify the components of production costs because of the increase in raw materials so that there is no efficiency in the raw materials. This research analyzes production net price determination and the influence of Material Cost and Production Labor Cost on the determination of selling price of PT Harrison & Gil Java Semarang. Path analysis is used in analyzing this research. Type of data that used is cross section from Februari to April 2018. The secondary data used in this research are material cost, production labor cost, production net price and selling price of frame products. Full costing method of production net price determination which consists of material cost and production labor cost. The result of data analysis states that Material Cost dan Production Labor Cost have positive influence toward Production Net Price. Futhermore, the influence of indirect effect for Material Cost towards Selling Price through Production Net Price is perfect mediation effect. Moreover, the highest value of elasticity for Production Net Price towards Selling Price which shows the cost efficiency. So, the company strives to focus on raw materials optimization and labor overtime restrictions for the cost efficiency.